Is Nature Our Ally? On the Debate Surrounding "Acts Against Nature" - Pachilla, Pablo (2025)
Starting from a diagnosis referring to the mutation of critical strategies visible in new materialisms, this paper explores the debate about so-called «acts against nature» from the positions of Karen Barad and Elizabeth Wilson. The problem concerns the relationship between nature and morality, whereas the differendum lies in the role of negativity. Finally, the work of Lorraine Daston is drawn upon to raise the question about the concept of nature at stake and the kinds of passions that are aroused when such natures are destabilized. I argue that the relationship between nature and normativity is inescapable, and thus propose to use the category of «naturemoral».